P216 RENAL RESISTANCE INDEX IS INDEPENDENTLY ASSOCIATED WITH THE WORSENING OF RENAL FUNCTION AFTER CORONARY ANGIOGRAPHY. (18th May 2022) - Goffredo, G; Barone, R; Di Terlizzi, V; Correale, M; Casavecchia, G; Ieva, R; Cuculo, A; Brunetti, N; Iacoviello, M
Abstract: Background: The term Cardiorenal Syndrome (CS) has been recently introduced to indicate the close relationship between cardiovascular and renal diseases, which are able to reciprocally influence the each other progression. In this setting the renal resistance index (RRI) has been demonstrated to be a useful parameter able to detect patients at higher risk of CS. However, there are no data about its role in predicting worsening of renal function (WRF) mediated by the intravascular administration of contrast. Aim of the Study: To evaluate the role of RRI in predicting WRF after coronary angiography. METHODS We enrolled 115 patients (mean age 64 years, 73% males, 84% hypertensive, 43% diabetic, 30% with acute coronary syndrome, 21% affected by chronic heart failure, CHF, with a mean left ventricular ejection fraction, LVEF, of 51±11) with suspected coronary artery disease, stable angina, or acute coronary syndromes who have been referred for coronary angiography (with or without pre–existing renal impairment). All patients underwent medical examination, electrocardiogram, echocardiographic and chemical evaluation, and renal arterial echo–color Doppler used to calculate RRI. WRF was defined as an increase of creatinine >0.3 mg/dl and of at least 25% from baseline 24–48 hours after coronary angiography. Results: After coronary angiography, 14 (12%) of the enrolled patients showed WRF. As shown in the Table, at univariate regression analysis baseline RRI was associated with WRF as well as age, peripheral artery disease, CHF, atrial fibrillation, NYHA class, LVEF, mitral regurgitation (MR), central venous pressure (CVP), tricuspid regurgitation (TR), estimated glomerular filtration rate (GFR). In a multivariate forward stepwise regression model, including all univariate predictors, history of CHF, high CVP and RRI were the only parameters significantly associated with WRF. Conclusion: Our findings demonstrate that in patients undergoing coronary angiography, history of CHF, high CVP and RRI are independent predictors of WRF. RRI, but not GFR, is independently associated with WRF probably because providing additional relevant information about cardiorenal pathophysiological factors reflecting the hemodynamic status and kidney flow reserve.